Potential Neuroprotective Effect of the Endocannabinoid System on Parkinson’s Disease - María Fernanda Urmeneta-Ortíz; Aldo Rafael Tejeda-Martínez; Orfil González-Reynoso; Mario Eduardo Flores-Soto (Parkinson's Disease)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by alterations in motor capacity resulting from a decrease in the neurotransmitter dopamine due to the selective death of dopaminergic neurons of the nigrostriatal pathway. Unfortunately, conventional pharmacological treatments fail to halt disease progression; therefore, new therapeutic strategies are needed, and currently, some are being investigated. The endocannabinoid system (ECS), highly expressed in the basal ganglia (BG) circuit, undergoes alterations in response to dopaminergic depletion, potentially contributing to motor symptoms and the etiopathogenesis of PD. Substantial evidence supports the neuroprotective role of the ECS through various mechanisms, including anti-inflammatory, antioxidative, and antiapoptotic effects. Therefore, the ECS emerges as a promising target for PD treatment. This review provides a comprehensive summary of current clinical and preclinical evidence concerning ECS alterations in PD, along with potential pharmacological targets that may exert the protection of dopaminergic neurons.